PENINGKATAN KETERAMPILAN MENULIS KARANGAN MELALUI MODEL ROLE PLAYING DENGAN MEDIA GAMBAR SERI PADA SISWA KELAS IV SDN 1 JERUKAGUNG TAHUN AJARAN 2016/2017 - Laila, Ratih; Suhartono, Suhartono; Joharman, Joharman (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: Improving Story-Writing Skill through Role Playing Model Using Series Picture as Media for Fourth Grade Students of SDN 1 Jerukagung  in The Academic Year of 2016/2017.The objective of this research was to improve story-writing skill for fourth-grade students of SDN 1 Jerukagung in the academic year of 2016/2017 through role playing model using the series picture as media. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were 21 fourth grade students of SDN 1 Jerukagung. The validity of data in this research was analyzed using triangulation of sources and triangulation of technique. The results of the study show that use of role playing model using the series picture as media can improve story-writing skill. Keywords: role playing, series picture as media, writing skill